2013
DOI: 10.1122/1.4804358
|View full text |Cite
|
Sign up to set email alerts
|

Stick–slip instabilities in the shear flow of magnetorheological suspensions

Abstract: SynopsysThis work is devoted to the stick-slip instabilities that appear in the shear flow of highly concentrated suspensions of magnetic microparticles. The effect of the applied magnetic field strength was analyzed in details. With this aim, homogeneous suspensions of iron microparticles with concentration near the limit of maximum-packing fraction were prepared, and shear-flow measurements were performed in a controlled-rate mode using a rheometer provided with a rough parallel-plate geometry. For each give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…This mechanism was later confirmed by particle level simulations of Klingenberg et al (1991) and Bonnecaze and Brady (1992). More recently, López-López et al (2013) have observed regular saw-tooth-like stress oscillations of a concentrated MR fluid sheared at a low constant shear rate and subjected to an external magnetic field perpendicular to the rheometer plates. These oscillations were accompanied by shear localization in the middle plane of the rheometer gap and occurred at low shear rates belonging to a decreasing part of the steadystate flow curve.…”
Section: Introductionmentioning
confidence: 64%
“…This mechanism was later confirmed by particle level simulations of Klingenberg et al (1991) and Bonnecaze and Brady (1992). More recently, López-López et al (2013) have observed regular saw-tooth-like stress oscillations of a concentrated MR fluid sheared at a low constant shear rate and subjected to an external magnetic field perpendicular to the rheometer plates. These oscillations were accompanied by shear localization in the middle plane of the rheometer gap and occurred at low shear rates belonging to a decreasing part of the steadystate flow curve.…”
Section: Introductionmentioning
confidence: 64%
“…Above the jamming transition, strong oscillations of the stress are observed if the shear rate is imposed (Lootens et al 2003) or of the shear rate if it is the stress which is imposed. This is also the case in yield stress fluids at low shear rate after yielding (Nagahiro et al 2013) In yield stress fluids different models can predict these oscillations by introducing a "structure variable" whose time evolution is coupled to the shear rate (Nagahiro et al 2013;Lopez-Lopez et al 2013;Head et al 2002). These oscillations are usually interpreted as resulting from an instability related to the negative differential viscosity which appears in the form of an S shape in the stress versus shear rate curve.…”
Section: V-oscillation Regime Above the Critical Stressmentioning
confidence: 99%
“…As observed, after an initial sharp increase of the shear stress, some saw-tooth-like oscillations appeared at low enough values of the imposed shear rate. In a previous work we studied the origin of these oscillations and showed that from a microscopic viewpoint they were the consequence of the periodic failure and healing of the field-induced particle structures [9]. In more details, we supposed the appearance of a periodic array of gap-spanning cylindrical columns.…”
Section: A Time Evolution Of the Shear Stressmentioning
confidence: 96%
“…For the application of the magnetic field we used solenoids placed co-axially with the measuring geometry, as described in [15]. The experimental protocol used for the rheological measurements is reported in details elsewhere [9]. Briefly, we proceeded as it follows.…”
Section: (I)mentioning
confidence: 99%
See 1 more Smart Citation